Japanese management abroad: A literature review and a research agenda - Enrique Yacuzzi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2011)
The purpose of this review is to evaluate the status of scholarly research on Japanese management as it is applied outside Japan. The first part of the review deals with the concept of Japanese management. The second part aims at understanding how Japanese management is applied in foreign countries, both at subsidiaries of Japanese corporations and in non-Japanese firms; in particular, the issue of transferability of concepts and techniques is considered in detail. Primarily EBSCO databases were used, but other sources were consulted as well. A set of seven steps was used to organize the literature search, analysis, and report. These steps, presented in a section on methodology, are: 1. Rationale; 2. Sampling results; 6. Interpretations, limitations, and implications; and 7. Reporting the review. There is general agreement among different authors on the main tenets of Japanese management (especially those referred to Human Resources Management) and on the ability of firms
Keywords: F23; M10; M11; M12; M14; P51; 330; Japanese management; Japanese management abroad; transferability of Japanese management; international corporations; multinational corporations; Japanese multinational corporations; Japanese and non-Japanese alike; Management; Multinationales Unternehmen; Japan